Single-cell sequencing combined with spatial transcriptomics reveals the characteristics of follicle-targeted inflammation patterns in primary cicatricial alopecia - Qitao Chen; Yuqian Li; Qilin Zhu; Zhongming Li; Guanghui Shao; Yanjun Liu; Peixuan Jiang; Qiuwei Tao; Lili Shen; Jing Zhu; Linwei Wei; Yanhua Li; et al. (Cell & Bioscience)
Abstract Background Primary cicatricial alopecia (PCA) causes irreversible hair loss due to immune-mediated hair follicle destruction. This study investigates follicle-targeted inflammation in lichen planopilaris (LPP), a major PCA subtype, to identify therapeutic targets. Methods Scalp samples from LPP, localized scleroderma (LS), and controls were analyzed using single-cell RNA sequencing and spatial transcriptomics. Cellular composition, spatial localization, and intercellular interactions were examined using differential gene expression and ligand-receptor analyses. Results CD8⁺ effector memory T cells (Tem) and macrophages infiltrated hair follicles in LPP, disrupting immune privilege and promoting scarring. Heightened interferon-γ (IFN-γ) signaling and STAT1 activation in Tem cells caused epithelial-mesenchymal transition (EMT) in hair follicle stem cells (HFSCs). Additionally, macrophage-secreted oncostatin M (OSM) impaired HFSC integrity. These mechanisms drive LPP’s inflammation and fibrosis. Conclusions Our findings identify interferon-γ and oncostatin M as key drivers of LPP pathogenesis, offering targets to reduce follicular scarring and preserve hair growth. Trial registration Not applicable. Graphical abstract